1996
DOI: 10.1111/j.1349-7006.1996.tb00194.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Aryl Hydrocarbon Hydroxylase and Polymorphisms of the CYP1A1 Gene

Abstract: We examined the relationship between aryl hydrocarbon hydroxylase (AHH) and the frequency of a Msp I mutation in the 3′‐flanking region of cytochrome P450 (CYP) 1A1 (Mspl polymorphism) and another mutation in exon 7 (Ile‐Val polymorphism) in 84 healthy male subjects in Fukuoka, Japan. AHH inducibility (3‐methylcholanthrene (MC)‐induced AHH activity/non‐induced AHH activity) was correlated with the MspI polymorphism (P<0.0001) and age class (P=0.015), whereas no correlation was found for the Ile‐Val polymorphis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
1
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(58 citation statements)
references
References 27 publications
0
56
1
1
Order By: Relevance
“…The T3801C and A2455G alleles were reported to encode an inducible form of CYP1A1 Kiyohara et al 1996). Although CYP1 enzymes are responsible for metabolically activating PAHs and aromatic amines, Nebert et al (2004) proposed that whether CYP1A1 detoxifies or causes toxicity depends on many factors, such as sub-cellular content and location, amount of Phase II metabolism, degree of coupling to Phase II enzymes, and cell type-and tissue-specific context, as well as pharmacokinetics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The T3801C and A2455G alleles were reported to encode an inducible form of CYP1A1 Kiyohara et al 1996). Although CYP1 enzymes are responsible for metabolically activating PAHs and aromatic amines, Nebert et al (2004) proposed that whether CYP1A1 detoxifies or causes toxicity depends on many factors, such as sub-cellular content and location, amount of Phase II metabolism, degree of coupling to Phase II enzymes, and cell type-and tissue-specific context, as well as pharmacokinetics.…”
Section: Discussionmentioning
confidence: 99%
“…Crofts et al (1993) reported a threefold elevation in CYP1A1 enzymatic activity associated with A2455G G/ G genotypes. The T3801C allele was also reported to encode an inducible form of CYP1A1 (Kiyohara et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…These two findings suggest that the inducible CYP1A1 gene might contribute to oesophageal cancer development. In two in vitro studies, Kiyohara et al (1996) examined the relationship between AHH inducibility (3-methylcholanthrene (MC)-induced AHH activity/non-induced AHH activity) and the frequency of CYP1A1 MspI and exon 7 polymorphisms in peripheral lymphocytes in 84 healthy Japanese male subjects in vitro. They found the ageadjusted AHH inducibility (mean+standard error) of the wildtype, heterozygous, and homozygous variants of the CYP1A1 MspI gene to be 4.89+0.36, 4.82+0.29, and 13.61+1.44, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Genotypic variation resulting in a phenotype that increases 2-OH may decrease risk of carcinogenesis by two possible mechanisms: competitively reducing potentially genotoxic 4-OH intermediates and increasing 2-OH intermediates, which can be methylated to 2-MeO-E2, an antiangiogenic metabolite (26). Functional studies have shown increased enzyme activity with m1 ''C,'' m2 Val 462 , and m3 ''C'' alleles and reduced activity with m4 Asn 461 allele (27)(28)(29)(30). Similar to results of previous studies, we observed no association between the CYP1A1 m1, m2, and m4 polymorphisms and epithelial ovarian cancer (9)(10)(11).…”
Section: Discussionmentioning
confidence: 99%